The theoretical basis of internal communication as an active process of information exchange - Zdravkovska, Suzana; Haque, Sabir (Technium Social Sciences Journal, 2023)
Communication is a broadly exploited concept or, more precisely, a social phenomenon for which in contemporary science there are various discursive approaches. But, regardless of the access discourse, in each of them, communication confirms the unconditionality of its existence as a prerequisite for the functioning of man as a being, and of society as a system. The approach used in this paper supports the thesis that information is the basis of communication, and hence communication is an active process of information exchange, the process of creating and exchanging messages within a network with mutually dependent relations. Referring to the theoretical aspects of communication as a process for information exchange, this paper puts special emphasis on internal communication and its essential importance for development, management and efficient functioning of an organization. The research done by analyzing different theoretical approaches to communication confirms the initial research hypothesis that communication and information are pair categories that inevitably go side by side, and exchange of information as a part of the communication process is of increasing importance, especially in the conditions when it brings and gives knowledge that corresponds to the needs of a particular individual, group or organization. Hence, well-established rules of internal communication from the aspect of information exchange have priority and are set as a condition for the successful functioning of an organization.